Coaching the horizontal jumps: Alternative mentality - Ghazaryan, S. (IFAC, 2013)
At the International Festival of Athletics Coaching from 25.-27. Oktober 2013 in Glasgow/Scotland the autor, athletics coach & manager of Armenia, reviews the evolution of the men`s long jump and triple jump Olympic chronology and the performance progression of the men`s long and triple jump as well as an alternative classification of world top athletes in men`s long jump and triple jump according to their results/PB, main skills (speed, jump, power) and jump technique. The author compares traditional skills & abilities and alternative skills & abilities. He explains how to identify talented and promising youths (traditionally/alternatively) and how to coach the horizontal jumps. Some words are given about the competitions and the competition rules.